Role of Endorectal Prostate MRI in Patients with Initial Suspicion of Prostate Cancer - Franiel, T.; Vargas, H. A.; Mazaheri, Y.; Böhmer, S.; Hricak, H.; Akin, O.; Beyersdorff, D. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: To evaluate the role of conventional endorectal prostate MRI in patients with initial suspicion of prostate cancer.Materials and Methods: Ethics board approval was received for this retrospective study of 87 men who underwent 1.5-Tesla conventional prostate MRI with a combination of endorectal and body phased-array coils for suspected prostate cancer before their first systematic 12-core TRUS-guided biopsy. Three radiologists independently analyzed the images, dividing the prostate into 12 regions corresponding to the biopsy scheme and scoring each region for the presence of prostate cancer on a 5-point scale. Results were analyzed by prostate region. ROC analysis was done and descriptive statistics were calculated. The negative predictive value, specificity, sensitivity and positive predictive value were calculated using dichotomized scores (benign tissue = scores of 1 and 2; malignant tissues = scores of 3, 4, and 5).Results: Biopsy revealed cancer in 47/87 patients (26 low-grade [Gleason score 6]; 21 high-grade [Gleason score ≥ 3 + 4]), and 184/1044 cores (77 low-grade and 107 high-grade) with a median of 3 positive cores per cancer patient (range 1 – 12). The areas under ROC curves were 0.65 – 0.67 for cancer detection by region overall and 0.75 – 0.76 for the detection of high-grade cancer by region. Statistic figures for the detection of all cancers/high-grade cancers by region were as follows: negative predictive value, 87.4 – 88.2 %/92.6 – 93.1 %; specificity, 72.3 – 79.4 %/71.5 – 79.8 %; sensitivity, 49.5 – 54.8 %/62.6 – 69.2 %; and positive predictive value, 29.3 – 34.0 %/29.4 – 34.7 %.Conclusion: In patients with suspected prostate cancer, negative MRI findings indicate the absence of high-grade prostate cancer on subsequent TRUS-guided 12-core biopsy with high probability. However, agreement between conventional 1.5-T endorectal prostate MRI and systematic 12-core TRUS-guided biopsy for the detection of prostate cancer appears to be moderate.Citation Format:
Keywords: prostate cancer; initial suspicion; MRI